Dominant ARL3-related retinitis pigmentosa. (4th March 2019) - Holtan, Josephine Prener; Teigen, Knut; Aukrust, Ingvild; Bragadóttir, Ragnheiður; Houge, Gunnar
ABSTRACT: Purpose : To clinically and genetically characterise a second family with dominant ARL3 -related retinitis pigmentosa due to a specific ARL3 missense variant, p.(Tyr90Cys). Methods : Clinical examination included optical coherence tomography, electroretinography, and ultra-wide field retinal imaging with autofluorescence. Retrospective data were collected from the registry of inherited retinal diseases at Oslo university hospital. DNA was analysed by whole-exome sequencing and Sanger sequencing. The ARL3 missense variant was visualized in a 3D-protein structure. Results : The phenotype was non-syndromic retinitis pigmentosa with cataract associated with early onset of decreased central vision and central retinal thinning. Sanger sequencing confirmed the presence of a de novo ARL3 missense variant p.(Tyr90Cys) in the index patient and his affected son. We did not find any other cases with rare ARL3 variants in a cohort of 431 patients with retinitis pigmentosa-like disease. By visualizing Tyr90 in the 3D protein structure, it seems to play an important role in packing of the α/β structure of ADP-ribosylation factor-like 3 (ARL3). When changing Tyr90 to cysteine, we observe a loss of interactions in the core of the α/β structure that is likely to affect folding and stability of ARL3. Conclusion : Our study confirms that the ARL3 missense variant p.(Tyr90Cys) causes retinitis pigmentosa. In 2016, Strom et al. reported the exact same variant in a mother and two children with RP, labelled ?RP83 in the OMIM database. Now the questionmark can be removed, and ARL3 should be added to the list of genes that may cause non-syndromic dominant retinitis pigmentosa.